The picturesque and the sublime : a poetics of the Canadian landscape - Glickman, Susan, 1953- (McGill-Queen's University Press, 1998)
"The Picturesque and the Sublime is a cultural history of two hundred years of nature writing in Canada, from eighteenth-century prospect poems to contemporary encounters with landscape. Arguing against the received wisdom (made popular by Northrop Frye and Margaret Atwood) that Canadian writers view nature as hostile, Susan Glickman places Canadian literature in the English and European traditions of the sublime and the picturesque." "Glickman argues that early immigrants to Canada brought with them the expectation that nature would be grand, mysterious, awesome - even terrifying - and welcomed scenes that conformed to these notions of sublimity. She contends that to interpret their descriptions of nature as "negative," as so many critics have done, is a significant misunderstanding. Glickman provides close readings of several important works, including Susanna Moodie's "Enthusiasm," Charles G.D. Roberts's Ave, and Paulette Jiles's "Song to the Rising Sun," and explores the poems in the context of theories of nature and art."--Jacket